Chronic workload, subjective arm health, and throwing injury in high school baseball players: 3-year retrospective pilot study - Mehta, S.; Tang, S.; Rajapakse, C.; Juzwak, S.; Dowling, B. (Sports Health: A Multidisciplinary Approach, 2022)
Background: Baseball workloads are monitored by pitch counts, appearances, innings per appearance, ball velocity, and distance, whereas current workload standards neglect throws made during nongame situations. The association between total workloads, subjective measures, and injury in baseball is poorly understood. The question remains whether baseball athletes are at higher risk of injury by throwing more often or if they generate injury resilience when appropriately transitioned into the higher demands of throwing. Hypothesis: Increased chronic load, along with subjective arm health measures, are related to decreased injury risk. Study Design: Clinical research. Level of evidence: Level 3. Methods: A total of 49 male baseball players (age 17.9 ± 0.4 years, height 181.8 ± 6.8 cm, body mass 80.6 ± 9.1 kg) competing at the varsity high school level were included in this 3-year retrospective data analysis from 2016 to 2019. Players wore the motusTHROW sleeve and sensor during all throwing activities. Results: A total of 898,492 throws and 9455 athletic exposures were captured with the motusTHROW sensors. There were 24 injuries recorded throughout the 3-year analysis, with 11 throwing-related and 13 non-throwing related injuries. Results of the 1-way analysis of variance found chronic load was significantly related to throwing-injury occurrence (P < 0.01). Six of the throwing-related injuries occurred when athletes had a chronic load greater than 11.3, marking 75th percentile across all observations. There was a relationship between arm health and throwing arm-related injury occurrence (P < 0.01). Higher chronic load was associated with increased throwing-related injuries even when adjusted for arm health (P = 0.01). Specifically, injuries were more likely to occur in pitchers (either as a combination player or pitcher only) with a chronic load greater than 9.2. Conclusion: This study revealed a significant relationship between chronic load, subjective arm health, and throwing-related injury in varsity high school baseball players. Contrary to our hypothesis, increased chronic load was associated with increased injury risk. However, subjective arm health measures remain a relevant factor in assessing injury risk. Normative data for this population also provide key information around positional demands along with overall demands of the sport during the competitive season and off-season.